2014
DOI: 10.1371/journal.pone.0106342
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Circulating S100B Blood Levels in Schizophrenia

Abstract: S100B is a calcium-binding protein secreted in central nervous system from astrocytes and other glia cells. High blood S100B levels have been linked to brain damage and psychiatric disorders. S100B levels have been reported to be higher in schizophrenics than healthy controls. To quantify the relationship between S100B blood levels and schizophrenia a systematic literature review of case-control studies published on this topic within July 3rd 2014 was carried out using three bibliographic databases: Medline, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 69 publications
4
45
0
Order By: Relevance
“…According to our results, S100 B was not found to be beneficial as a marker of ASD. S100 B has been used as a marker and treatment response criterion in mood disorders and schizophrenia (Aleksovska et al, 2014; Schroeter et al, 2013; Yelmo‐Cruz et al, 2013). To date two studies have identified high levels of S100 B in ASD (Al‐Ayadhi and Mostafa, 2012; Shaker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, S100 B was not found to be beneficial as a marker of ASD. S100 B has been used as a marker and treatment response criterion in mood disorders and schizophrenia (Aleksovska et al, 2014; Schroeter et al, 2013; Yelmo‐Cruz et al, 2013). To date two studies have identified high levels of S100 B in ASD (Al‐Ayadhi and Mostafa, 2012; Shaker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from metanalysis concluded that levels of S100B are elevated in patients with mood disorders and schizophrenia and that levels of S100B were not affected by psychotropic medication. (Schroeter et al, 2009; Schroeter & Steiner, 2009; Aleksovska et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is defined as the "imbalance between the systemic manifestation of reactive oxygen species and the body's ability to eliminate the reactive oxygen species (ROS)" (Kohen and Nyska, 2002;Muller and Schwarz, 2010). Oxidative stress may also affect lipid and glucose metabolism in psychosis (Aleksovska et al, 2014). The innate immune system generates ROS and reactive nitrogen species (RNS) to assist with the destruction of foreign pathogens (Nathan and Shiloh, 2000).…”
Section: Oxidative Stress and Reactive Oxygen Speciesmentioning
confidence: 99%